Spermatocytic tumor associated with metastases: report of a rare case and literature review - Chen, Jianbai; Mou, Xiaorong; Zhang, Zhiming; Zhang, Wei; Nie, Zhiyong; Gao, Xiaoping; Gao, Yanyao; Qiu, Jianxin (Frontiers in Pharmacology, 2025)
Spermatocytic tumor (ST) is an exceedingly rare testicular neoplasm with non-specific clinical presentations, requiring histopathological confirmation for diagnosis. Radical orchiectomy remains the cornerstone of treatment, achieving favorable outcomes in most cases. However, early metastasis observed in some patients emphasizes the necessity of comprehensive systemic staging at diagnosis and rigorous postoperative surveillance. Current evidence is largely derived from case reports, limiting robust clinical guidance. Herein we present a case of pure testicular ST with synchronous multiple pulmonary metastases managed at Tangdu Hospital. Despite undergoing radical orchiectomy followed by chemotherapy, the patient exhibited disease progression. Additionally, we performed a literature review of published ST cases to summarize its clinicopathological features, treatment paradigms, and prognostic patterns. This study highlights the challenges in managing advanced ST and underscores the need for standardized therapeutic protocols.